The discovery of potent and selective kynurenine 3-monooxygenase inhibitors for the treatment of acute pancreatitis. Issue 9 (1st May 2017) - Liddle, John; Beaufils, Benjamin; Binnie, Margaret; Bouillot, Anne; Denis, Alexis A.; Hann, Michael M.; Haslam, Carl P.; Holmes, Duncan S.; Hutchinson, Jon P.; Kranz, Michael; McBride, Andrew; Mirguet, Olivier; et al.
Graphical abstract: Abstract: A series of potent, competitive and highly selective kynurenine monooxygenase inhibitors have been discovered via a substrate-based approach for the treatment of acute pancreatitis. The lead compound demonstrated good cellular potency and clear pharmacodynamic activity in vivo .